Influência dos protocolos de fotoativação na microdureza e no grau de conversão de uma resina composta - Bomfim, Andréa Galvão Marinho (2009)
This study evaluate the degree of conversion of composite resin Filtek Z 350 (3M ESPE), on shade A3, using halogen light VIP (Variable Intensity Polymerizer) Junior (Bisco) utilizing three light curing protocols, they are: standard 500mW/cm² by 40 sec; soft start 300mW/cm² by 3 sec and after 500mW/cm² by 30 sec; pulse delay 300mW/cm² by 3 sec, stop by 3 min and 100mW/cm² by 30 sec. The degree of conversion of the resin was analyzed by the test of microhardness Knoop and Raman spectrography. Five samples of each type of protocol for the microhardness test had been confectioned and one sample of each protocol for the test of Raman. The tests had been made 24 hours after the polymerization of the samples, that had been stored the dry one, protected from the light and at room temperature. In the microhardness, five indentations had been made in each surface (top and bottom) of the sample with a load of 10gf for 10s. The Raman was obtained from the center of the sample of the top and the bottom surfaces. The results had been submitted the Two-Way ANOVA and to the test of multiple comparisons of Student-Newman-Keuls, to a level of significance of 5%. It can be observed that it had statistical significant differences between the used curing protocols when the analysis was made in the top of specimens, being that the standard curing protocol presented biggest values of hardness. However, when the value of the hardness was obtained from in the opposing extremity of specimens (bottom), statistical significant differences between the curing protocols had not been observed. In the comparisons between the values of hardness observed in relation to the localization of the indentation, it can be observed independently that the values obtained in the top of specimens had been statistical differences, with exception for the protocol pulse delay, where had not significant statistical difference between the surfaces of top and bottom. The test of Raman confirmed the results finds in the microhardness, with the degree of conversion of resin higher in top surface, and with bigger degree of conversion of the conventional and soft start protocols.